MANAGING PROPERTY AND FACILITIES IN HIGHER EDUCATION INSTITUTIONS - Wan Zahari Wan Yusoff (Penerbit UTHM, 2016)
Property and facilities management is a vast area in the real estate discipline. Managing property and facilities particularly in Higher Education Institutions is complex and there is dearth of empirical literature in this aspect. This book comprehensively discusses important and current issues involved in property and facilities management in Higher Education Institutions. It is a rich sources of information based on recent research in a Malaysian University. It is a much-needed contribution to the literature on property and facilities management in tertiary education Institutions.